Factors Affecting Rural Youth Interest in Agriculture in Sindangkasih Ciamis District - Lukman Effendy; Ait Maryani; Ayu Yulia Azie (Jurnal Penyuluhan, 2020)
A study on farmer regeneration has been carried out in Sindangkasih Subdistrict, Ciamis in April - July 2019 with the aim of the study: (1) to describe the extent of youth interest in agriculture, (2) find factors that influence youth interest, and (3) formulate an improvement strategy youth interest. This quantitative descriptive study involved 79 young people as respondents from 3,158 people. Data collection using a questionnaire containing closed questions in accordance with the variables and research indicators that have been tested for validity and reliability. Descriptive analysis is carried out to provide an overview of youth interests, while to identify influential factors, multiple linear regression analysis is performed. The results showed (1) youth's interest in agriculture is included in the sufficient category, (2) youth's interest is influenced by external factors (extension activities, availability of resources, government support) and motivational factors (rewards, achievements, demands of life) with the Y model = - (0.051) + (0.457) X2 + (0.419) X3, and (3) strategies for increasing interest begin with facilitating youth in non-formal education (training / courses), and involving youth in agricultural program.